Impact of institutions on cross-border price dispersion - Jiří Schwarz (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper analyzes the role of institutions in price dispersion among cities in the European region in the 1996-2009 period. An overview of the literature on the border effect reveals that the role of institutions is completely neglected. Using the Worldwide Governance Indicators as explanatory variables I find that the better the institutions, the lower the predicted dispersion. The result is robust to different specifications of the regression model and it is consistent with a hypothesis that arbitrage, as an entrepreneurial activity and the main power behind the law of one price, is influenced by institutional quality.
Keywords: D23; E31; F41; L26; 330; border effect; price dispersion; price convergence; law of one price; institutional quality; Preisdifferenzierung; Preiskonvergenz; Institutionelle Infrastruktur; Systemvergleich; Europa